Melatonin inhibits HCC progression through regulating the alternative splicing of NEMO - Bai, Lu; Sun, Siwen; Su, Wenmei; Chen, Chaoqun; Lv, Yuesheng; Zhang, Jinrui; Zhao, Jinyao; Li, Man; Qi, Yangfan; Zhang, Wenjing; Wang, Yang (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is one of the most common primary cancers with limited therapeutic options. Melatonin, a neuroendocrine hormone produced primarily by the pineal gland, demonstrates an anti-cancer effect on a myriad of cancers including HCC. However, whether melatonin could suppress tumor growth through regulating RNA alternative splicing remains largely unknown. Here we demonstrated that melatonin could inhibit the growth of HCC. Mechanistically, melatonin induced transcriptional alterations of genes, which are involved in DNA replication, DNA metabolic process, DNA repair, response to wounding, steroid metabolic process, and extracellular matrix functions. Importantly, melatonin controlled numerous cancer-related RNA alternative splicing events, regulating mitotic cell cycle, microtubule-based process, kinase activity, DNA metabolic process, GTPase regulator activity functions. The regulatory effect of melatonin on alternative splicing is partially mediated by melatonin receptor MT1. Specifically, melatonin regulates the splicing of IKBKG (NEMO), an essential modulator of NF-κB. In brief, melatonin increased the production of the long isoform of NEMO-L with exon 5 inclusion, thereby inhibiting the growth of HepG2 cells. Collectively, our study provides a novel mechanism of melatonin in regulating RNA alternative splicing, and offers a new perspective for melatonin in the inhibition of cancer progression.